2015
DOI: 10.1111/jems.12105
|View full text |Cite
|
Sign up to set email alerts
|

Information Sharing in Contests

Abstract: We study the incentives to share private information ahead of contests, such as markets with promotional competition, procurement contests, or R&D. We consider the cases where …rms have (i) independent values and (ii) common values of winning the contest. In both cases, when decisions to share information are made independently, sharing information is strictly dominated. With independent values, an industry-wide agreement to share information can arise in equilibrium. Expected e¤ort is lower with than without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 52 publications
(52 reference statements)
0
23
1
Order By: Relevance
“…Our paper is also related to the literature on players' incentive to acquire and share information in different auction formats, such as Persico (), Yildirim (), Compte and Jehiel (), Szech (), Morath and Münster (), Denter, Morgan, and D. Sisak (), and Kovenock, Morath, and Münster (). In particular, in contrast to this paper, Denter, Morgan, and Sisak () consider one‐sided asymmetric information in an all pay setting.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our paper is also related to the literature on players' incentive to acquire and share information in different auction formats, such as Persico (), Yildirim (), Compte and Jehiel (), Szech (), Morath and Münster (), Denter, Morgan, and D. Sisak (), and Kovenock, Morath, and Münster (). In particular, in contrast to this paper, Denter, Morgan, and Sisak () consider one‐sided asymmetric information in an all pay setting.…”
mentioning
confidence: 99%
“…In spite of the difficulty in explicitly characterizing the bidding strategies, Serena successfully identifies the disclosure policy that generates the highest expected 13. Our paper is also related to the literature on players' incentive to acquire and share information in different auction formats, such as Persico (2000), Yildirim (2005), Compte and Jehiel (2007), Szech (2011), Morath and Münster (2013), Denter, Morgan, and D. Sisak (2014), and Kovenock, Morath, and Münster (2015). In particular, in contrast to this paper, Denter, Morgan, and Sisak (2014) consider one-sided asymmetric information in an all pay setting.…”
mentioning
confidence: 99%
“…Cf. Denter et al (2014) and Kovenock et al (2015). For an introduction to the burgeoning literature on all-pay contests, see Konrad (2009). nent that the battle will be excessively unequal, thereby inducing the stronger player to choose a more moderate strategy.…”
Section: Introductionmentioning
confidence: 99%
“…13 Speci…cally, Kovenock et al (2015) showed that, regardless of whether valuations are private or common, the interim information sharing game followed by an all-pay auction admits a perfect Bayesian equilibrium in which no player ever shares her private information. The present analysis is complementary to that of Kovenock et al (2015) in the sense that, instead of the all-pay auction, we consider a probabilistic contest. Overall, the review of the literature suggests that the speci…c research question pursued in the present paper, viz.…”
Section: Introductionmentioning
confidence: 99%
“…() in the context of lobbying, by Kovenock et al . () in all‐pay auctions, and by Gill () and Gordon () in R&D races. Mediated communication is studied by Hörner et al .…”
mentioning
confidence: 99%